1995
DOI: 10.1063/1.114046
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene formation during production of chemical vapor deposited diamond

Abstract: Large-scale and low-cost synthesis of single-walled carbon nanotubes by the catalytic pyrolysis of hydrocarbons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Literature also exists describing the creation of fullerenes in soot by hot-® lament chemical vapour deposition (CVD) techniques during diamond production, although in contrast to our work the substrate temperature was reported to be at least 850 ë C, with the precursor gases including a large fraction of hydrogen (Chow et al 1995). Interestingly, another detailed study has concluded that rf-PECVD is not a suitable method for producing C 60 thin ® lms ( Rocabois et al 1996).…”
Section: Please Scroll Down For Articlecontrasting
confidence: 65%
“…Literature also exists describing the creation of fullerenes in soot by hot-® lament chemical vapour deposition (CVD) techniques during diamond production, although in contrast to our work the substrate temperature was reported to be at least 850 ë C, with the precursor gases including a large fraction of hydrogen (Chow et al 1995). Interestingly, another detailed study has concluded that rf-PECVD is not a suitable method for producing C 60 thin ® lms ( Rocabois et al 1996).…”
Section: Please Scroll Down For Articlecontrasting
confidence: 65%
“…Nanotubes can be converted to a diamond-like super-hard material only under high temperature and high-pressure treatment. 8 We also note that vigorous sonication in CH 2 Cl 2 can damage the sides of MWCNTs and the extent of structural deformation is solventdependent. 9 In the presence of strong electric fields, carbon nanotubes decay by unraveling monatomic carbon "wires" from the exposed end.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the past decade has seen developments in the performance optimization of thin films by altering the deposition parameters. This has allowed for improved film characteristics without additional cost and spurred research into the growth and optimization of organic semiconductors [3][4][5][6]. Further, CVD and CBD have facilitated efficient device manufacturing by enabling systematic film layer depositions.…”
Section: Introductionmentioning
confidence: 99%